INTEGRATION OF TARBAWI HADITH IN THE DEVELOPMENT OF INTELLECT, HEART, AND SOUL IN ELEMENTARY SCHOOL AT SDAL-FALAH BOARDING SCHOOL - Pipih Santora; Qorie Hizratul Muttaqie; Achmad Nurdiyansah; Maslani; Hamdan Maulana; Hofifah Astuti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research investigates the integration of Tarbawi Hadith in the development of intellect (ʿaql), heart (qalb), and soul (nafs) among elementary students at SD Al-Falah Boarding School. The study adopts a qualitative case study approach, utilizing classroom observations, in-depth interviews with teachers, and document analysis to explore how Tarbawi Hadith is embedded within the school’s educational practices. The findings reveal that the systematic inclusion of selected prophetic traditions into the curriculum not only enhances students’ cognitive abilities but also nurtures their emotional intelligence and spiritual awareness. Teachers employ various strategies, such as reflective discussions, storytelling, and value-based activities, to internalize the messages of the Hadith and encourage students to apply them in daily life. The integration process is supported by a school culture that emphasizes character building, discipline, and a strong sense of community. As a result, students demonstrate improved moral reasoning, empathy, self-control, and a deeper understanding of Islamic values. The study highlights the pivotal role of Tarbawi Hadith as a source of holistic education, fostering balanced development across intellectual, emotional, and spiritual domains. It also identifies challenges, such as the need for ongoing teacher training and curriculum development, to ensure the effective implementation of integrative approaches. The research offers practical recommendations for Islamic educational institutions seeking to cultivate well-rounded individuals through the meaningful incorporation of religious